Generation of a homozygous ABCA7 knockout cell line (AHMUCNi002-A) in human iPSCs using CRISPR/Cas9 - Juanjuan Li; Letian Yin; Chengwei Wang; Yin Xu (Stem Cell Research)
ABCA7, located on chromosome 19, encodes an ATP-binding cassette transporter. Loss-of-function variants of ABCA7 are associated with an increased risk of Alzheimer’s disease. To explore the role of ABCA7 deficiency in the pathogenesis of Alzheimer’s disease, CRISPR/Cas9 genome-editing technology was utilized to generate a homozygous ABCA7 knockout in human induced pluripotent stem cells (hiPSCs). The resulting ABCA7 knockout cell line exhibited normal pluripotency, a stable karyotype, and the ability to differentiate into all three germ layers.